Where does the time go when children don't sleep? A randomized crossover study. Issue 3 (27th December 2022) - Morrison, Silke; Haszard, Jillian J.; Galland, Barbara C.; Jackson, Rosie; Meredith‐Jones, Kim A.; Elder, Dawn E.; Taylor, Rachael W.
Abstract: Objective: This study aimed to describe how mild sleep deprivation in children changes time spent physically active and sedentary. Methods: In 2018 through 2020, children ( n  = 105) with normal sleep were randomized to go to bed 1 hour earlier (extension) or 1 hour later (restriction) than their usual bedtime for 1 week, each separated by a 1‐week washout. Twenty‐four‐hour movement behaviors were measured with waist‐worn actigraphy and expressed in minutes and proportions (percentages). Mixed‐effects regression models determined mean differences in time use (95% CI) between conditions. Time gained from sleep lost that was reallocated to other movement behaviors in the 24‐hour day was modeled using regression. Results: Children ( n  = 96) gained ~49 minutes of awake time when sleep was restricted compared with extended. This time was mostly reallocated to sedentary behavior (28 minutes; 95% CI: 19‐37), followed by physical activity (22 minutes; 95% CI: 14‐30). When time was expressed as a percentage, the overall composition of movement behavior remained similar across both sleep conditions. Conclusions: Children were not less physically active when mildly sleep deprived. Time gained from sleeping less was proportionally, rather than preferentially, reallocated to sedentary time and physical activity. These findings suggest that decreased physical activity seems unlikely to explain the association between short sleep and obesity in children.